STUDY ON THE ADSORPTION PROPERTIES OF NOVEL CALIX[6]ARENE POLYMERS FOR HEAVY METAL CATIONS - Susy Yunita Prabawati; Jumina Jumina; Sri Juari Santosa; Mustofa Mustofa; Keisuke Ohto (Universitas Gadjah Mada, 2012)
A research has been conducted to investigate the capability of a series of novel calix[6]arenes-based polymers: poly-monoallyloxycalix[6]arene (2a), poly-monoallyloxypenta-estercalix[6]arene (2b) and poly-monoallyloxypenta-acidcalix[6]arene (2c) for trapping of heavy metal cations such as Cd(II), Cu(II) and Cr(III). The existence of active hydroxy group (-OH) and with a tunnel-like structure of the polymers, caused the polymers can be used as adsorbents for heavy metals. The adsorption process was carried out in batch method in the variation of acidity (pH), contact time and initial concentration of metal ions. The results showed that the amount of adsorbed metal increased with the increasing of the pH of metal solution. For these three polymers, the amount of metal ions Cd(II), Cu(II) and Cr(III) adsorbed was optimum at pH 7, 6 and 5 respectively. The optimum contact time for Cd(II) and Cu(II) was 120 min, while that for Cr(III) was 60 min. Study of the adsorption kinetics showed that the adsorption of Cd(II), Cu(II) and Cr(III) using polymer 2a followed kinetics model of Ho. For adsorbent 2b and 2c, the adsorption kinetics of Cd(II) and Cr(III) also followed kinetics model of Ho while for the Cu(II) followed Lagergren kinetic models. Isothermal studies showed that the adsorption of metal ions on all adsorbents tend to follow the Langmuir isotherm. The adsorption energies of the three adsorbents were higher than 23 kJ/mole and polymer 2c has the largest adsorption capacity for Cr(III).